Synthesis, characterization and partition coefficients for VOC vapor adsorption onto novel pyridine derivatives Co(II) phthalocyanines - ABDURRAHMANOĞLU, ŞAZİYE (ELSEVIER SCIENCE SA, 2017)
In this study, novel pyridine derivatives Co(II) phthalocyanines were synthesized in two steps. In the first step, initial compounds 4-(4-methylpyridin-2-yloxy) phthalonitrile (3) and 3-(4-methylpyridin-2-yloxy) phthalonitrile (3') were prepared by the reaction of 2-hydroxy-4-methyl-pyridin (2) with 4-nitrophthalonitrile (1) and 3-nitrophthalonitrile (17, respectively. In the second step, compounds 3 and 3' reacted with Co(OAc)(2)center dot 4H(2)O to obtain 2(3),9(10),16(17),23(24)-tetrakis[4-methylpyridin-2-yloxylphthalociyaninato cobalt(II) (4) and 1(4),8(11),15(18),22(25)-tetrakis[4-methylpyridin-2-yloxy]phthalociyaninato cobalt(II) (4'). The influence of the substituent position on the organic vapor sensing performance towards 5 different groups of analytes (alkanes, chlorinated hydrocarbons, amines, alcohols and aromatics) were examined. Due to the complex nature of the VOC vapor and phthalocyanine interactions quartz crystal microbalance was used as transducer. Sensors coated by spray deposition technique showed linear dependence on analyte concentration with good reversibility, response and recovery times. Partition coefficient was used as descriptor in order to compare the sensing performance of the compounds. Results showed that the magnitude of the frequency shifts strongly depend on the position of the substituent unit.
Keywords: Phthalocyanine; Recovery; Soluble; Vapor sensing; Pyridine; Cobalt; SANDWICH DILUTETIUM TETRAPHTHALOCYANINE; CATALYSIS; SENSORS